The nexus of CSR and co-creation: a roadmap towards consumer loyalty - Naveed Ahmad; Miklas Scholz; Zia Ullah; Muhammad Zulqarnain Arshad; Raja Irfan Sabir; Waris Ali Khan (MDPI, 2021)
Corporate Social Responsibility (CSR) is regarded as an effort to be undertaken by the businesses to contribute towards society at large positively. The idea behind the concept of CSR is that businesses are required to pursue the notion of pro-social objectives along with economic objectives. Research has long established that corporate social responsibility, along with its philanthropic nature, can also produce extraordinary marketing results for businesses. The relationship between CSR and consumer loyalty is well acknowledged in extant literature. Likewise, involving consumers through co-creation in the product/service development process may provide an exciting experience to consumers, which is likely to influence their loyalty. With these arguments, the present research investigates the impact of CSR on consumer loyalty with the mediating role of co-creation in the banking sector of an emerging economy such as Pakistan. Structural equation modeling (SEM) is used for data analysis in the present study. The results validate that CSR improves consumer loyalty, and co-creation partially mediates this relationship. The results of the current survey will help banking institutions to identify how they can develop core strategic considerations based on CSR and co-creation.